Autonomous Landing of a Fixed-Wing UAV With RTK GNSS and MEMS IMU - Lu Xia; Jianqing Li (International Journal of Aerospace Engineering)
Autonomous landing system is an important part of unmanned aerial vehicle (UAV) autonomous flight. Large fixed-wing UAVs often consume more onboard space and computing resources. With the improvement of system integration and the reduction of high-performance global navigation satellite system (GNSS) costs, real-time kinematic (RTK) GNSS has been widely used in small-scale and low-cost fixed-wing UAVs. This article uses less onboard hardware and ground facility requirements to design an autonomous taking off and landing system suitable for general fixed-wing UAVs. A modified gradient descent attitude estimator, based on microelectromechanical system (MEMS) inertial measurement unit (IMU) and RTK GNSS, and a guidance method based on a tracking differentiator for using in a high dynamic environment are proposed, and circular path following and vertical transient simulations are performed. The simulation results show that this method can improve attitude estimation accuracy, motion control accuracy, and altitudinal transient quality. Finally, the actual flight test verifies its feasibility in the actual environment. The flight test results prove that it is feasible to implement the autonomous landing process of fixed-wing UAV with the proposed system and method.